Conflict Variety and the Facilitation Role of Forest Managemen Unit (FMU) on Resolution of Tenurial Conflict - Golar , Golar Golar; Hasriani, Hasriani Muis; Wahyu , Wahyu Syahputra Simorangkir (Forestry Department, University of Muhammadiyah Makassar, 2022)
In this study, tenure conflict is interpreted as various forms of claims related to mastery, management, utilization, and land use at FMU areas of Dampelas Tinombo. In this context, the FMU will be directly and responsibly involved in addressing disputes in its territory. This research aims to identify and analyze the variety of land-use conflicts and how the role of FMU in resolving conflict resolution in its managed areas. This study was conducted in 2020 at FMU of Dampelas Tinombo using the Rapid Land Tenure Assessment (RA-TA) method. Data collection techniques with a Rapid Rural Appraisal (RRA) approach through in-depth interviews and focus group discussions. The study sample was established by purposive sampling. The results showed that the variety of conflicts in FMU was land clearing, threats of illegal logging activities, and low public trust in programs derived from FMU. The role of KPH is needed in the resolution of tenure conflicts, significantly facilitating in optimizing collaborative management of forest resources and reducing the implementation of social forestry in the form of empowerment schemes and forestry partnerships.